ANALYSIS OF DIFFERENTIAL GENE EXPRESSION USING THE LIMMA PACKAGE - Doroshenko, Iryna; Plotnikova, Olha (SWorld-Ger Conference proceedings, 2025)
The article presents an analysis of differential gene expression using the limma package in the R environment on a dataset containing 2000 genes and 62 tissue samples (22 normal and 40 tumor samples). Various normalization methods and test correction tech